Effect of Sperm Selection by ’’Swim-Up" Technique on the Sex Ratio of In Vitro Produced Ovine Embryos: Saja Hadi and Ihsan H. AL-Timimi - Hadi, Saja (The Iraqi Journal of Veterinary Medicine, 2013)
The objective of this study was to investigate the percentage of male and female ovine embryos produced after oocytes fertilization by sperm selected with self-migration (swim-up) technique. The sex of in vitro produced embryos was determined by Polymerase chain reaction (PCR). results indicate that the fertilization by sperm selected using Swim-up technique was 81.8% (9/11) male and 18.1% (2/11) female in vitro produced embryos when centrifuged at 200×g, while centrifugation at 300×g was 72.7% (8/11) male and 27.2% (3/11) female embryos. It was concluded that the use of “swim-up” technique refer to significant (P<0.05) occurred for increasing male embryos ratio compared with normal ratio (50%) which represent the sex, and it is for the first time, preselected sperms used for In Vitro fertilization (gender selection) in farm animals in Iraq.